Penguatan Komunikasi Interpersonal, Kepuasan Kerja dan Komitmen Organisasi untuk Meningkatkan Kinerja Guru [Strengthening Interpersonal Communication, Job Satisfaction and Organizational Commitment to Improve Teacher Performance] - Hennyta, Violent; Junita, Junita; Riyanti, Riyanti; Sipayung, Mario Asido (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2023)
The importance of teachers' performance in education is emphasized, outlining their roles in planning, implementing, and evaluating learning activities. Factors influencing teacher performance, such as interpersonal communication, job satisfaction, and organizational commitment, are the focus of this research. This study is deemed significant due to the adverse effects of declining teacher performance on the quality of education, learning motivation, and academic achievement. This study used quantitative methods, including surveys and simple linear regression, to analyze the impact of independent variables on a dependent variable. The research involved 43 teachers from Christian elementary schools in Bekasi. Data was collected using a Likert scale with validated instruments, followed by tests for normality and linearity. Hypothesis testing utilized the t-test, and SPSS 26 for calculations. In efforts to enhance teacher performance, strengthening interpersonal communication, job satisfaction, and organizational commitment are crucial. Schools should prioritize these aspects to maintain a positive reputation in the community by having professional teachers. Teachers with good performance instill trust in parents to enroll their children in the school. Effective teacher performance results in student achievements and boosts community confidence in the school. The suggestion for schools is to prioritize these variables to create a positive impact on students, parents, and the community, thereby establishing schools with professional teachers.